Shoreline development and degradation of coastal fish reproduction habitats - Sundblad, Göran (Ambio, 2014)
Coastal development has severely affected habitats and biodiversity during the last century, but quantitative estimates of the impacts are usually lacking. We utilize predictive habitat modeling and mapping of human pressures to estimate the cumulative long-term effects of coastal development in relation to fish habitats. Based on aerial photographs since the 1960s, shoreline development rates were estimated in the Stockholm archipelago in the Baltic Sea. By combining shoreline development rates with spatial predictions of fish reproduction habitats, we estimated annual habitat degradation rates for three of the most common coastal fish species, northern pike (Esox lucius), Eurasian perch (Perca fluviatilis) and roach (Rutilus rutilus). The results showed that shoreline constructions were concentrated to the reproduction habitats of these species. The estimated degradation rates, where a degraded habitat was defined as having ≥3 constructions per 100 m shoreline, were on average 0.5 % of available habitats per year and about 1 % in areas close to larger population centers. Approximately 40 % of available habitats were already degraded in 2005. These results provide an example of how many small construction projects over time may have a vast impact on coastal fish populations.